LEGAL PROTECTION FOR VIDEO CONTENT CREATORS ON SOCIAL MEDIA THAT ARE REUPLOADED TO THE FACEBOOK PRO PLATFORM BASED ON MUI FATWA NUMBER 1 OF 2003 CONCERNING COPYRIGHT - Andini Eka Putri; Annisa Sativa (Program Pascasarjana UIN Sumatera Utara, 2026)
Reuploading is the activity of re-uploading other content creators videos on social media. Facebook is one platform that is starting to gain popularity. With the introduction of Meta's newest feature, Facebook Professional, which allows for commissions upon account monetization. The phenomenon of reuploading video content on social media, particularly on the Facebook Pro platform, has raised issues of copyright infringement and economic losses for the original creators, as many creators re-upload other creators' videos without permission for commercial purposes. This study aims to examine legal protection for creators of videos that are re-uploaded without permission based on MUI Fatwa Number 1 of 2003. The research uses an empirical juridical approach to examine the application of law in social life and legal norms of the practice of re-uploading video content creators on the Facebook Pro platform based on MUI Fatwa Number 1 of 2003 and Law Number 28 of 2014. The results of this study indicate that the reason Facebook Pro creators reupload other content creators' videos without permission is for account monetization. MUI Fatwa Number 1 of 2003 explicitly states that all forms of copyright infringement, including piracy, are haram and constitute injustice because they harm the creator's economic rights. Creators who reupload other content creators' videos without permission, even removing watermarks for commercial purposes, must pay the original video owner for economic rights. Therefore, this study concludes that MUI Fatwa Number 1 of 2003 explicitly states that all forms of copyright infringement, including piracy, are haram and constitute an unjust act because they harm the creator's economic rights.